Middle Education and continuity of education in Uruguay: A case study - Albornoz, Alejandra; González, María Cristina; Domínguez, Malena; Baccino, Mariela; Rodríguez, Schubert; Tarde, Sheyla (Profesorado, Revista de Currículum y Formación del Profesorado, 2015)
The following work describes the Social Representations from the involved actors in a vocational educational experience. The vocational educational experience aims to motivate the continuation of the education of young adults in a rural location in Uruguay. Through the Social Representations build by the social actors it is sought to know if the re-attachment process for the young adults to the educative system was effective. We used a case study; by using a semi structured interviews we gather the information and studied with Content Analysis. The results show that the young adults feel they are part of the process; they respond with interest and obtain satisfactory performance on their respective educational levels. Behind the success of this educational experience there is a diversification of the curriculum; didactic work from a strong group of teachers and the presence of social networks.